OCCURRENCE AND DOMINANCE OF AN INVASIVE TOXIN PRODUCING MARINE CYANOBACTERIA INTO MANGROVE ENVIRONMENT OF THE POTENGI RIVER ESTUARY, IN NATAL, RIO GRANDE DO NORTE STATE, BRAZIL - Chellappa, Naithirithi T.; Lima, A.KA.; Chellappa, Thiago (Arquivos de Ciências do Mar, 2017)
This paper describes a general account of phytoplankton and the occurrence and dominance of Harmful Algal Species (HAB) of a cyanobacterium, Nodularia sp. to an environmentally impacted Potengi estuary of Natal, Rio Grande do Norte State of Brazil. It represents an analysis of decline of phytoplankton diversity, increased chlorophyll concentrations and the time and duration of the persistence of Nodularia sp. A fixed site was chosen near the Navy Base for the entire study period and the study was made in two different periods, one before (1990-1997) and one after (2000-2001) the period of environmental changes in the mangrove environment of the Potengi estuary to distinguish changes in phytoplankton diversity. The data on temperature, salinity, inorganic nutrients, sewage influx and the deforestration were computed for statistical analysis together with the data on phytoplankton species diversity and the levels of chlorophyll a concentrations. The results indicate the reduction in phytoplankton diversity with the extinction of an important diatom, Skeletonema costatum, the species highly required by the planktonic larvae for their growth. The growth condition of toxic bloom formation of Nodularia sp. and fish kill incidence hás been investigated. Finally, the triggering mechanism of bloom formation was discussed.